Proses Pengecoran Logam Menggunakan Media Cetakan Plastisin Dengan Bahan Timah - Sembiring, Perdy; Girsang, Evan Roland; Ginting, Dicka Prasetya; Hermanto, Tino (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Metal casting is a manufacturing process that uses molten metal and molds to produce shapes that closely resemble the final geometry of a finished product. The molten metal is poured or pressed into a mold cavity that matches the desired shape or design. The objective of this research is to create a mold pattern using plastilin as a medium, identify the defects in the casting results, evaluate the advantages and disadvantages of using plastilin molds, and determine the shrinkage that occurs in the cast product. The research method applied in this metal casting process is the experimental method, where the mold is made from plastilin. The results show that the casting process led to several defects in the final product. The observed defects include porosity, a rough surface, and shrinkage. The porosity defects, characterized by small holes, were caused by trapped air during the pouring of the molten metal. The rough surface was due to the plastilin mold melting when the molten metal was poured into the mold. It can be concluded from this study that using plastilin as a mold medium is less effective, as the plastilin mold melts during the casting process, resulting in many casting defects. The pouring temperature affects the level of porosity in the casting, where higher pouring temperatures lead to increased porosity.